KAJIAN EFISIENSI PEMASARAN KUBIS (Brassica oleracea) STUDI KASUS DI KELOMPOK TANI SUMBER MAKMUR DESA CONTO KECAMATAN BULUKERTO KABUPATEN WONOGIRI - ROHMAWAN HENDRIASTO; MTH HANDAYANI; SUSWADI SUSWADI; KUSRIANI PRASETYOWATI (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2019)
This study aims to determine the marketing channelâ€™s function, marketing margins and economic efficiency of cabbage plants (Brassica oleracea) in Sumber Makmur farmer groups. The study was conducted in April to May 2018 in the Conto Village, Bulukerto Subdistrict, Wonogiri Regency with a altitude of 750 meters above sea level. This study uses the method of determining the area by purposive sampling, determining the respondents using random sampling and snowball sampling for the marketing channel method.Â The data used are primary and secondary data. Data collection techniques were carried out by observation, interview recording and questionnaire. The results showed that in the Sumber Makmur farmer group there were three marketing channels, the largest total marketing costs at the marketing channel I (Rp. 845.00 / kg) and the lowest total marketing costs at the marketing channel III (Rp. 152.00 / kg). The biggest total profit on the marketing channel II (Rp. 2,276.30 / kg) and the lowest total profit on the Marketing III channel (Rp. 628.77 / kg). Marketing channel II margin is the largest margin (Rp. 2,698.30 / kg) and the lowest marketing channel margin is in marketing channel III (Rp. 780.77 / kg). Farmer's largest share is in marketing channel III (77.77%) and the lowest share share on marketing channel II (51.04%). The cabbage marketing channel in the most efficient Sumber Makmur farmer group in the Village of Buloerto Subdistrict is in the marketing channel III, from farmers to small traders and then to the final consumers.